2018
DOI: 10.3389/fimmu.2018.02082
|View full text |Cite
|
Sign up to set email alerts
|

Complex Network of NKT Cell Subsets Controls Immune Homeostasis in Liver and Gut

Abstract: The liver-gut immune axis is enriched in several innate immune cells, including innate-like unconventional and adaptive T cells that are thought to be involved in the maintenance of tolerance to gut-derived antigens and, at the same time, enable effective immunity against microbes. Two subsets of lipid-reactive CD1d-restricted natural killer T (NKT) cells, invariant NKT (iNKT) and type II NKT cells present in both mice and humans. NKT cells play an important role in regulation of inflammation in the liver and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 81 publications
1
30
2
Order By: Relevance
“…Another component of innate immunity implicated in NAFLD and NASH is NKT cells, which are a T cell subset characterized by the coexpression of T cell receptor and NK cell surface receptors (NK1.1 in mice and CD161 or CD56 in humans) 70 . NKT cells recognize lipid antigens presented by CD1d-expressing antigenpresenting cells (APCs) and secrete a variety of cytokines (IL-4, IL-10, IFNγ and TNF) that can promote T H 1, T H 2 and CD4 + CD25 + regulatory T (T reg ) cell activities 70 . Thus, NKT cells can both stimulate and suppress immune and/or inflammatory responses.…”
Section: Innate and Adaptive Cell Interplaymentioning
confidence: 99%
See 1 more Smart Citation
“…Another component of innate immunity implicated in NAFLD and NASH is NKT cells, which are a T cell subset characterized by the coexpression of T cell receptor and NK cell surface receptors (NK1.1 in mice and CD161 or CD56 in humans) 70 . NKT cells recognize lipid antigens presented by CD1d-expressing antigenpresenting cells (APCs) and secrete a variety of cytokines (IL-4, IL-10, IFNγ and TNF) that can promote T H 1, T H 2 and CD4 + CD25 + regulatory T (T reg ) cell activities 70 . Thus, NKT cells can both stimulate and suppress immune and/or inflammatory responses.…”
Section: Innate and Adaptive Cell Interplaymentioning
confidence: 99%
“…Interfering with NKT cells during advanced NASH effectively improves hepatic parenchymal injury, inflammation and fibrosis in different experimental models of the disease 30,47,74,75 . The large majority (95%) of liver NKT cells is represented by type I or invariant NKT (iNKT) cells 70 . Interestingly, the lack of iNKT cells in Jα18 -/mice or their inhibition in wild-type animals treated with the retinoic acid receptor-γ agonist tazarotene reduces CD8 + T cell infiltration in the livers of these mice with NASH 75 , suggesting a strict interplay between cytotoxic T cells and iNKT cells in the mechanisms supporting steatohepatitis (Fig.…”
Section: Innate and Adaptive Cell Interplaymentioning
confidence: 99%
“…Using mouse models, two studies in 2006 first demonstrated the ability of NK cells in killing activated HSCs (25,46). Other different studies in animal models (47)(48)(49)(50)(51)(52)(53) as well as in human patients (54,55) have also confirmed this result. Further studies have suggested that the killing ability of NK cells is based on the activation status of HSCs: early activated (transitional) HSCs are killed by NK cells, while quiescent or fully activated HSCs are usually not.…”
Section: Nk Cellsmentioning
confidence: 86%
“…As a specialized subset of T cells that recognize lipids or glycolipid presented by CD1d rather than peptides, they express a large number of markers of receptors on both NK cells and T cells (49,50). Natural killer T cells can rapidly secrete innumerable pro-inflammatory and anti-inflammatory cytokines (Th1 or Th2 type) and act on other innate cells as well as adaptive T and B cells (51). Many studies have considered that invariant Natural killer T (iNKT) cells play a part in hepatic fibrogenesis.…”
Section: Nkt Cellsmentioning
confidence: 99%
“…Functionally distinct NKT cell effector subpopulations, primed to secrete unique combinations of cytokines and defined by particular transcription factor expression patterns, potently modulate disparate aspects of immunity [49][50][51][52] . In this present study, we uncovered a small population of NKT cells that expressed low levels of the transcription factor YY1.…”
Section: Discussionmentioning
confidence: 99%